Load and distinctness interact in working memory for lexical manual gestures - Rudner, Mary; Toscano, Elena; Holmer, Emil (Frontiers in Psychology, 2015)
The Ease of Language Understanding model (Rönnberg et al., 2013) predicts that decreasing the distinctness of language stimuli increases working memory load; in the speech domain this notion is supported by empirical evidence. Our aim was to determine whether such an over-additive interaction can be generalized to sign processing in sign-naïve individuals and whether it is modulated by experience of computer gaming. Twenty young adults with no knowledge of sign language performed an n-back working memory task based on manual gestures lexicalized in sign language; the visual resolution of the signs and working memory load were manipulated. Performance was poorer when load was high and resolution was low. These two effects interacted over-additively, demonstrating that reducing the resolution of signed stimuli increases working memory load when there is no pre-existing semantic representation. This suggests that load and distinctness are handled by a shared amodal mechanism which can be revealed empirically when stimuli are degraded and load is high, even without pre-existing semantic representation. There was some evidence that the mechanism is influenced by computer gaming experience. Future work should explore how the shared mechanism is influenced by pre-existing semantic representation and sensory factors together with computer gaming experience.